Effects of watching violent cartoon movies on the aggressive behavior of children. - Yu, Oliver Francis T. (1999.)
This study investigated the relationship hypothesized to exist between watching violent cartoon movies and the aggressive behavior of children. The participant were randomly selected elementary pupils from a learning center enrolled during SY 1997-1998. The instrument used were the films Snow White and the Seven Dwarfs for the control group and the Dragon Ball Z for the experimental group. The Pretest - Postest Control Group design was used for the experimental method. A content analysis on the short stories written by the participants was made to determine the presence/absence of aggression. Analysis of Variance was used to establish if there is any significant difference between the two groups. The findings of this study showed that watching of violent cartoon movies affect the aggressive behavior of children.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Cartoon Movies, Effects -- Children